Bilateral Nuclear Cataract with Deferasirox in a Patient of Beta-thalassemia: A Case Report and Literature Review - Tushit Dhar; Vaishali Tomar; Subhash Dadeya (Delhi Journal of Ophthalmology)
We report the case of a 15-year-old child with beta-thalassemia developing bilateral cataracts while receiving deferasirox, a newer iron chelator. She had been taking deferasirox for the past 10 years while receiving monthly blood transfusions. A slit-lamp examination revealed a central cataract having nuclear morphology in both eyes. Lenticular opacities in beta-thalassemia patients typically do not involve the visual axis and are known to correlate positively with deferoxamine and deferiprone. With deferasirox increasingly superseding deferoxamine as an oral chelator, we delineate the morphology of cataract possible with it. Understanding the likelihood of cataracts with this newer drug will help to anticipate and prevent their development, thus avoiding visual deterioration in already debilitated thalassemia patients.